2011
DOI: 10.1029/2011jd016530
|View full text |Cite
|
Sign up to set email alerts
|

Beryllium-10 transport to Antarctica: Results from seasonally resolved observations and modeling

Abstract: Cosmogenic 10Be measured in polar ice cores has important application in the reconstruction of past solar activity. However, the processes controlling its atmospheric transport and deposition to the ice sheets are not fully understood. Here we use the seasonal changes in 10Be concentrations in a 10 year monthly resolved ice core record from the Law Dome site (East Antarctica) in conjunction with ECHAM5‐HAM general circulation model (GCM) simulations of 10Be and 7Be deposition as tools to examine this problem. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
37
1

Year Published

2013
2013
2017
2017

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(42 citation statements)
references
References 79 publications
4
37
1
Order By: Relevance
“…10. Comparison of modelled tritium in precipitation with surface snow samples from two ITASE Antarctic traverses (Proposito et al, 2002;Becagli et al, 2004) and some pre-bomb measurements. (a) Antarctic map from the "0.2TU_MB−30%" simulation and (b) zooming in the area of interest.…”
Section: Influence Of Isotopic Fractionation On the Continental Effectmentioning
confidence: 99%
See 1 more Smart Citation
“…10. Comparison of modelled tritium in precipitation with surface snow samples from two ITASE Antarctic traverses (Proposito et al, 2002;Becagli et al, 2004) and some pre-bomb measurements. (a) Antarctic map from the "0.2TU_MB−30%" simulation and (b) zooming in the area of interest.…”
Section: Influence Of Isotopic Fractionation On the Continental Effectmentioning
confidence: 99%
“…Focusing on the tritium distribution over the Antarctica, we therefore also considered tritium data of surface snow samples (1 m depth integrated sample) from two ITASE (International TransAntarctic Scientific Expedition) traverses (Proposito et al, 2002;Becagli et al, 2004), carried out during the Southern Hemisphere summers of 1998/99 and 2001/02. Tritium concentration was measured by liquid scintillation counting (Proposito et al, 2002) and the associated errors range from ±1 TU (2σ ) at background levels, to ±3 TU at the level of 35 TU. These traverses connected wellknown East-Antarctic sites such as Terre Adélie, Terra Nova Bay, Dome C and Talos Dome.…”
Section: Description Of the Available Tritium Datamentioning
confidence: 99%
“…From Greenland, five ice cores fulfill our criteria: Milcent (Beer, Raisbeck, and Yiou, 1991), Dye-3 (Beer et al, 1990), Camp Century (Beer et al, 1988), GRIP (Muscheler et al, 2004;Yiou et al, 1997) and NGRIP (Berggren et al, 2009). As mentioned in the introduction, variations in ice-core 10 Be concentrations do not only reflect fluctuations in the 10 Be production rates, but may also be influenced by changes in atmospheric circulation, aerosol transport, and deposition (Adolphi and Muscheler, 2016;Field et al, 2006;Pedro et al, 2011Pedro et al, , 2012Pedro et al, , 2006. For example, it has been suggested that volcanic aerosols influence the scavenging of 10 Be, i.e.…”
Section: Be Datamentioning
confidence: 99%
“…It is worthy to note that the two curves show an excellent agreement with each other over the 20th century. Prior to this period, the two curves appear not to show similar solar cycle variations, which is likely due to regional climatic effects (Usoskin et al 2009) leading to strong fluctuations of the 10 Be deposition (Pedro et al 2006(Pedro et al , 2011.…”
Section: Centennial Reconstructions and Radionuclide Productionmentioning
confidence: 99%
“…essential at interannual-decadal time scales (Pedro et al 2006(Pedro et al , 2011Usoskin et al 2009). …”
Section: Centennial Reconstructions and Radionuclide Productionmentioning
confidence: 99%